THE RELATIONSHIP BETWEEN LEARNING MOTIVATION, PROFESSIONAL COURSES AND PASS RATES OF SKILLS CERTIFICATION: A CASE STUDY OF VOCATIONAL SENIOR HIGH SCHOOL STUDENTS IN TAIWAN - Zhi Rong Chen, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study investigates the relationship between learning motivation, professional courses performance, and the pass rates of skills certification among students in vocational senior high schools in Taiwan. In response to the growing demand for professional competencies in the labor market, skills certification has become a crucial indicator of students’occupational readiness and a determinant of their future career trajectories.The research employed a questionnaire method to collect data regarding students’learning motivation, professional courses performance, and skills certification outcomes .A quantification method was adopted, utilizing descriptive statistics, correlation analysis, and logistic regression analysis to examine the relationships among the core variables.The results indicate a statistically significant positive relationship between professional courses performance and the pass rates of skills certification, confirming course performance as a key predictive factor. While learning motivation was positively correlated with course performance, it did not exhibit a statistically significant direct effect on certification outcomes.Additionally, different preparation strategies were found to impact course performance significantly. Among these, participation in after-school programs and group study demonstrated the most favorable outcomes. These findings provide empirical insights into how instructional design and preparatory practices can enhance students’performance in professional courses and increase their likelihood of success in skills certification.The study recommends integrating simulated certification exercises and diversified instructional resources into professional courses to optimize learning outcomes and improve certification pass rates across the vocational education system in Taiwan.